Predictive Factors of Intestinal Necrosis in Acute Mesenteric Ischemia: Prospective Study from an Intestinal Stroke Center. (April 2017) - Nuzzo, Alexandre; Maggiori, Leon; Ronot, Maxime; Becq, Aymeric; Plessier, Aurelie; Gault, Nathalie; Joly, Francisca; Castier, Yves; Vilgrain, Valerie; Paugam, Catherine; Panis, Yves; Bouhnik, Yoram; et al.
Abstract : Objectives: To identify predictive factors for irreversible transmural intestinal necrosis (ITIN) in acute mesenteric ischemia (AMI) and establish a risk score for ITIN. Methods: This single‐center prospective cohort study was performed between 2009 and 2015 in patients with AMI. The primary outcome was the occurrence of ITIN, confirmed by specimen analysis in patients who underwent surgery. Patients who recovered from AMI with no need for intestinal resection were considered not to have ITIN. Clinical, biological and radiological data were compared in a Cox regression model. Results: A total of 67 patients were included. The origin of AMI was arterial, venous, or non‐occlusive in 61%, 37%, 2% of cases, respectively. Intestinal resection and ITIN concerned 42% and 34% of patients, respectively. Factors associated with ITIN in multivariate analysis were: organ failure (hazard ratio (HR): 3.1 (95% confidence interval (CI): 1.1–8.5); P =0.03), serum lactate levels >2 mmol/l (HR: 4.1 (95% CI: 1.4–11.5); P =0.01), and bowel loop dilation on computerized tomography scan (HR: 2.6 (95% CI: 1.2–5.7); P =0.02). ITIN rate increased from 3% to 38%, 89%, and 100% in patients with 0, 1, 2, and 3 factors, respectively. Area under the receiver operating characteristics curve for the diagnosis of ITIN was 0.936 (95% CI: 0.866–0.997) depending on the number of predictive factors. Conclusions: We identified three predictive factors for irreversible intestinal ischemic injury requiring resection in the setting of AMI. Close monitoring of these factors could help avoid unnecessary laparotomy, prevent resection, as well as complications due to unresected necrosis, and possibly lower the overall mortality.